1993
DOI: 10.1029/93gl02727
|View full text |Cite
|
Sign up to set email alerts
|

The Beaufort Sea continental shelf as a seasonal source of atmospheric methane

Abstract: Methane concentrations in the Beaufort Sea under the winter ice canopy offshore from northern Alaska are 3 to 28 times greater than they are in late summer when the ice is absent in a similar region offshore from northern Canada where methane is in approximate equilibrium with the atmosphere. These observations suggest that methane concentrates in the water under the sea-ice cover during winter and ventilates rapidly in late summer as the ice melts and retreats. Conditions similar to those on the Beaufort Sea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
46
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 20 publications
6
46
0
Order By: Relevance
“…These works assist in understanding the biological controls on oceanic methane and may contribute to establishing baselines to monitor change in marine sediments. This may be of particular importance in the Arctic Ocean due to its sensitivity to climate change and abundance of methane (Kvenvolden et al, 1993;McGuire et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These works assist in understanding the biological controls on oceanic methane and may contribute to establishing baselines to monitor change in marine sediments. This may be of particular importance in the Arctic Ocean due to its sensitivity to climate change and abundance of methane (Kvenvolden et al, 1993;McGuire et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, because planktonic prokaryotes are primarily free-living on the ABS, (Garneau et al, 2009) it is reasonable to propose that the stratified period provides an opportunity to observe hydrographic influences on sediment microbiomes. Another factor making the ABS a candidate for study is the abundant methane in shelf and slope sediments (Kvenvolden et al, 1993;McGuire et al, 2009), which permits examination of methane-containing sediments in contact with water of Atlantic or Pacific origin but in close geographic proximity. Because of these features, the influence of water dispersal, the physical environment and local geochemistry on microbiome structure can be parsed.…”
Section: Introductionmentioning
confidence: 99%
“…(2012) reported methane supersaturation in Arctic surface waters and point to sediments as being the main source. Several studies have suggested that methane accumulates in Arctic waters underlying sea ice, where it can be subsequently oxidized (Kitidis et al, 2010;Kvenvolden et al, 1993;Savvivech et al, 2004;Shakova et al, 2010). While methane oxidation is one of the known sinks for methane, the future retreat of the Arctic sea-ice cover could limit the residence time of methane in the water column and the subsequent rates of methane oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Of that marine contribution, 75 % is from coastal regions (Bange et al, 1994). CH 4 supersaturation relative to the atmosphere in estuaries (Borges and Abril, 2011;Upstill-Goddard et al, 2000) and coastal shelves (Kvenvolden et al, 1993;Savvichev et al, 2004;Shakhova et al, 2005Shakhova et al, , 2010 is indeed larger than that in the open ocean (Bates et al, 1996;Damm et al, 2007Damm et al, , 2008Damm et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Many CH 4 measurements have been carried out in sediments and seawater throughout the coastal Arctic areas (Kvenvolden et al, 1993;Savvichev et al, 2004;Shakhova et al, 2005Shakhova et al, , 2010. These observations have led to speculations about potential CH 4 accumulation (Shakhova et al, 2010) and/or oxidation (Kitidis et al, 2010) under sea ice cover.…”
Section: Introductionmentioning
confidence: 99%